2019
DOI: 10.1155/2019/4071762
|View full text |Cite
|
Sign up to set email alerts
|

Solid Indeterminate Nodules with a Radiological Stability Suggesting Benignity: A Texture Analysis of Computed Tomography Images Based on the Kurtosis and Skewness of the Nodule Volume Density Histogram

Abstract: Background The number of incidental findings of pulmonary nodules using imaging methods to diagnose other thoracic or extrathoracic conditions has increased, suggesting the need for in-depth radiological image analyses to identify nodule type and avoid unnecessary invasive procedures. Objectives The present study evaluated solid indeterminate nodules with a radiological stability suggesting benignity (SINRSBs) through a texture analysis of computed tomography (CT) images. Methods A total of 100 chest CT scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Some authors have discussed the theoretical basis of skewness and kurtosis and questioned the reliability and usability of those parameters 14,22 . On the other hand, several recently published studies have used these metrics (e.g., for tumor differentiation) and, upon evaluating their repeatability and correlations with clinical findings, have reported promising results 23–25 . Based on these findings, kurtosis may be regarded as a reliable biomarker with certain clinical potential if the analyzed data set is sufficiently large.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have discussed the theoretical basis of skewness and kurtosis and questioned the reliability and usability of those parameters 14,22 . On the other hand, several recently published studies have used these metrics (e.g., for tumor differentiation) and, upon evaluating their repeatability and correlations with clinical findings, have reported promising results 23–25 . Based on these findings, kurtosis may be regarded as a reliable biomarker with certain clinical potential if the analyzed data set is sufficiently large.…”
Section: Discussionmentioning
confidence: 99%
“…There were no validation sets and area under the curve (AUC) were high, ranging between 0.864-0.93. A more recent study looking at only kurtosis and skewness showed differences between benign and malignant nodules; however, AUC was only approximately 0.7 for both features and no combined model was explored (52).…”
Section: Predicting Benign Vs Malignant Nodulesmentioning
confidence: 92%
“…There were no validation sets and area under the curve (AUC) were high, ranging between 0.864-0.93. A more recent study looking at only kurtosis and skewness showed differences between benign and malignant nodules; however, AUC was only approximately 0.7 for both features and no combined model was explored (52). Some early studies also looked at derived features from unsupervised methods.…”
Section: Predicting Benign Vs Malignant Nodulesmentioning
confidence: 99%